Análise proteômica do fungo patogênico humano Fonsecaea pedrosoi, cultivado nas condições de temperatura de 22º C e 36º C - Lima, Davi Vinícius de (2017)
The Polymorphic fungus Fonsecaea pedrosoi is the main etiological agent of Chromoblastomycosis (CBM), characterized as a chronic cutaneous mycotic infection, occurring mainly in tropical regions. The limited availability of effective therapeutic protocols coupled with CBM clinical polymorphism lead to often prolonged and high relapse rate therapies. Results regarding the molecular biology of F. pedrosoi are scarce however, some virulence factors have already been described, evidencing the need to explore the mechanisms used by this pathogen during infection. The present work carried out in silico analyzes under specific culture conditions, with temperatures of 22º C and 36º C, aiming to better understand the proteome of this fungus, both intracellular and secreted. In order to identify these proteins, we used bioinformatic tools that are available online and allowed the prediction of protein sets that can be secreted by classical and non-classical routes. After the in silico prediction method, proteins were identified in the fungal extracts by the Ultraperformance Liquid Chromatography coupled to Mass Spectrometry (UPLC-MSE) methodology. Those identified in the extracts that brought a more reliable interpretation corroborated the results in silico. The proteins identified stand out for being related to various biological processes, such as metabolism of carbon compounds, energy, proteins related to thermal and oxidative stress, defense, proteins related to the cell cycle, among other functions. The analyzes showed that the vast majority of identified proteins are secreted by alternative pathways, and the results point to the great importance of the biological roles that these secreted proteins can play during the onset of infection. Thus, we observed that the fungus presents variations in protein expression levels according to the condition addressed and may reflect on its behavior and responses to the successful establishment of the infection.